The Brokenwood mysteries. A merry bloody Christmas [videorecording (DVD)] - Rea, Neill, 1971-; Sutherland, Fern; Sampson, Nic, 1986- (Acorn Media, 2019)
A quirky New Zealand mystery that follows Dl Mike Shepherd, who arrives in the seemingly peaceful town of Brokenwood with a classic car, a country music collection, and an indeterminate number of ex-wives. Shepherd soon discovers that Brokenwood is full of secrets and suspicions. In this Christmas episode, the mayor is murdered in his home after the annual holiday parade, and Shepherd and his assistant Kristin Sims must solve a Christmas murder.